Peningkatan Minat Sastra Melalui Keterampilan Menulis Cerpen di SMPN Satu Atap 4 Purba Sumatera Utara - Ulfah Julianti; Budi Mulia; Desi Karolina Saragih; Bram Denafri (Universitas Pamulang, 2021)
Learning to write can be started by reading. In addition to reading, the improvement of writing skills is also determined by motivational factors that come from within the writer because writing cannot be separated from activities that are continuously nurtured and developed. For this reason, we from the PKM Team, Sasindo Unpam lecturers, carried out outreach activities with the theme